Career management, Employee Retention - Sari Rahayu (Jurnal Ekonomi dan Bisnis Digital, 2024)
The development and growth of a company depends on quality human resources which can be obtained through employee training and development programs. Employee development is the target of training so that employees will be competent in carrying out their duties and can improve employees' skills, knowledge and experience in their work so that they can support their careers in the future. Career is a basic need for employees to gain social recognition in the family and economy. A career consists of all the jobs a person holds during his or her work. Some employees' work is part of a plan. Career management is the process of managing an employee's career which includes the stages of career planning activities, career development and counseling, as well as career decision making. Organizations can also support employees by creating an environment that enables growth and development amidst rapid change.